APUNTES SOBRE LOS CONTRATOS ATÍPICOS O INNOMINADOS - Ugarte Vega Centeno, Máximo Alfredo (2010)
It should be noted first that this work is divided into two parts, the first was published in this magazine in issue 25 and in this issue N ° 26 present the second part of “Notes on atypical contracts or Unnamed” . Today we live in modern times and changes are fast-paced, motivated primarily by the globalization that has brought us new concepts primarily for the information, knowledge and technology that will be shared widely and increasingly we are more interconnected by innovative technologies, expansion of markets and communications inevitably generate lifestyle changes of people and as a result of their relationships. These events generate parallel the emergence of new contractual links that are not within the traditional legal codes or written. The law can not be outside the regulation of these new legal contract governing these relations, hence its importance and necessity of use of such atypical contracts or unnamed is a reality and its use has become commoditized. In these contracts innominate or atypical today often comes to be safer than other contracts, and not petrified in its forms, but instead is constantly evolving by the dynamism of the economy and trade that generates creativity the resolution of contractual legal issues in this regard develop trust contracts, Joint Venture and Atypical Underwiriting which are contracts and are the product of two things: Either they are mere invention of the parts where two men agree and make a contract that had never been before or will be after the contract or contracts are typically mixtures already listed or regulated by laws or codes.